Testing and analysis of a 60 degrees swept back wing with ribs parallel to the line of flight - Howe, D. (College of Aeronautics, Cranfield, 1953)
The specimen used in this work represents the load carrying structure of a cambered two spar 60 degree sweptback wing, having closely pitched ribs of large boom area parallel to the line of flight, and thick skins. Continues …